The Effect Of Financial Literacy And Life Style On Gen Z Consumptive Behavior In Ngawi Regency Through Selt Efficacy As An Intervening Variable - Putri, Rika Ananda; Harianto, Kukuh; Sutapa, Heru (Jurnal Mamangan, 2023)
This study aims to examine the effect of financial literacy and life style on the consumptive behavior of Gen Z Ngawi district through self efficacy as an intervening variable. The data used in this study is primary data which is obtained directly from respondents by distributing questionnaires online via google form. Sampling using nonprobability sampling techniques with a purposive sampling approach there were 100 samples of Gen Z in Ngawi Regency. The data analysis method in this study uses partial least square (PLS) with the help of SmartPLS software. The results of this study indicate that: Financial literacy has no influence on consumptive behavior, Life style has a significant positive effect on consumptive behavior, Self efficacy has a significant positive effect on consumptive behavior, Financial literacy has a significant positive effect on self efficacy, Life style has a significant positive effect on self efficacy, Financial literacy has a significant positive effect on consumptive behavior through self efficacy, Life style has a significant positive effect on consumptive behavior through self efficacy..